Penerapan Sistem Akuntansi Instansi Berbasis Akrual (SAIBA) Pada Satuan Kerja Pusat Pengendalian Lumpur Sidoarjo - Asadi, Asadi; Sulistiyowati, Yayuk (Journal of Indonesian Economic Research, 2023)
This study aims to test how the Sidoarjo Sludge Control Center applies the Accrual-Based Accounting Application System (SAIBA) in the preparation of financial statements. Research is a type of qualitative research with methods, namely: summarizing, choosing the main things, focusing on important things, looking for themes and patterns and discarding unnecessary (data reduction), displaying data or commonly referred to as presenting data, drawing conclusions and verification. Results and discussion: The Sidoarjo Sludge Control Center Work Unit has implemented the SAIBA application to prepare financial statements in accordance with the following excerpts of interviews with SAIBA operators: Since PPLS was established in 2017, we have implemented SAIBA to prepare financial statements. The preparation of financial statements using SAIBA is in accordance with applicable regulations, because SAIBA has accommodated current regulations, both from the Minister of Finance and Government Regulations. In the application of the SAIBA application, obstacles were found, namely the difference between journals formed by SIMAK BMN and MAK capital expenditure as conveyed by the SIMAK BMN Operator that journals formed by SIMAK BMN were often incompatible type of MAK capital expenditure, Road, Irrigation and Network (JIJ) expenditure becomes Equipment and Machinery or Building Assets so that it appears that the BMN transaction journal has not been adjusted. Conclusion: The Sidoarjo Sludge Control Center Work Unit has implemented the SAIBA application well in preparing its financial statements in accordance with government accounting standards. Penelitian ini bertujuan untuk menguji bagaimana Pusat Pengendalian Lumpur Sidoarjo menerapkan Sistem Aplikasi Akuntansi Berbasis Akrual (SAIBA) dalam penyusunan laporan keuangan. Penelitian merupakan jenis penelitian kualitatif dengan metode yaitu : merangkum, memilih hal-hal yang pokok, memfokuskan pada hal yang penting, dicari tema dan polanya dan membuang yang tidak perlu (reduksi data), mendisplaykan data atau biasa disebut dengan penyajian data, penarikan kesimpulan dan verifikasi. Hasil dan diskusi: Satuan Kerja Pusat Pengendalian Lumpur Sidoarjo telah menerapkan aplikasi SAIBA untuk menyusun laporan keuangan sesuai   dengan wawancara dengan operator SAIBA berikut : Sejak PPLS dibentuk  Tahun 2017 kami sudah menerapkan SAIBA untuk menyusun laporan keuangan. Penyusunan laporan keuangan menggunakan SAIBA sudah sesuai dengan peraturan yang berlaku, karena SAIBA sudah mengakomodasi peraturan-peraturan  yang  sedang berlaku,  baik dari Menteri Keuangan maupun Peraturan Pemerintah. Dalam penerapan aplikasi SAIBA, ditemukan kendala  yaitu  adanya  perbedaan  jurnal  bentukan  SIMAK  BMN dengan MAK belanja modal seperti yang disampaikan oleh Operator SIMAK  BMN  bahwa  jurnal  bentukan  SIMAK  BMN yang  sering tidak  sesuai  dengan  jenis  MAK  belanja  modalnya,  belanja  Jalan, Irigasi dan Jaringan (JIJ) menjadi Aset Peralatan dan Mesin atau Gedung sehingga muncul jurnal transaksi BMN belum disesuaikan. Kesimpulan: Satuan  Kerja  Pusat  Pengendalian  Lumpur  Sidoarjo  telah  menerapkan aplikasi SAIBA dengan baik dalam penyusunan laporan keuangannya yang sesuai dengan standar akuntansi pemerintahan.